Design and development of adsorption desalination system - Chua, Kheng Lim (2014)
Waste heat driven adsorption desalination systems offer great potential in solving the shortage of fresh water. This report presents the design and development of the new two-bed adsorption desalination system as well as the design of the four-bed non-regenerative adsorption desalination system.